Socioeconomic position and intergenerational associations of ideal health behaviors. (October 2019) - Komulainen, Kaisla; Mittleman, Murray A; Jokela, Markus; Laitinen, Tomi T; Pahkala, Katja; Elovainio, Marko; Juonala, Markus; Tammelin, Tuija; Kähönen, Mika; Raitakari, Olli; Keltikangas-Järvinen, Liisa; Pulkki-Råback, Laura
Background: Promoting ideal cardiovascular health behaviors is an objective of the American Heart Association 2020 goals. We hypothesized that ideal health behaviors of parents are associated with health behaviors of their adult offspring, and that higher socioeconomic position in either generation enhances intergenerational associations of ideal health behaviors. Design: Prospective cohort study. Methods: We included 1856 Young Finns Study participants who had repeated measurements of socioeconomic position (education, income, occupation), smoking status, body mass index, physical activity and diet from 2001, 2007 and 2011, and data on parental socioeconomic position and health behaviors from 1980. We calculated the total number of ideal behaviors in both generations using American Heart Association definitions. Intergenerational associations were examined using ordinal and linear multilevel regression with random intercepts, in which each participant contributed one, two or three measurements of adult health behaviors (2001, 2007, 2011). All analyses were adjusted for offspring sex, birth year, age, parental education and single parenthood. Results: Overall, parental ideal health behaviors were associated with ideal behaviors among offspring (odds ratio (OR) 1.28, 95% confidence interval 1.17, 1.39). Furthermore, ORs for these intergenerational associations were greater among offspring whose parents or who themselves had higher educational attainment (OR 1.56 for high vs. OR 1.19 for low parental education; P  = 0.01 for interaction, OR 1.32 for high vs. OR 1.04 for low offspring education; P  = 0.02 for interaction). Similar trends were seen with parental income and offspring occupation. Results from linear regression analyses were similar. Conclusions: These prospective data suggest higher socioeconomic position in parents or in their adult offspring strengthens the intergenerational continuum of ideal cardiovascular health behaviors.